Grey matter alterations in obesity: A meta‐analysis of whole‐brain studies. (10th December 2018) - Herrmann, Martin J.; Tesar, Ann‐Katrin; Beier, Jennifer; Berg, Max; Warrings, Bodo
Summary: Obesity is a major problem in the modern world causing a higher risk for various cerebrovascular diseases causing a profound individual and societal burden. The neurobiological foundation bears potential to understand the complex interaction of individual differences in brain structure and function and ingestive behaviour. This systematic review was performed on the current evidence of structural abnormalities in grey matter volume (GMV) in patients with obesity based on studies published until December 2017, which were selected through search in PubMed, CENTER (Cochrane Library), PsycINFO, Web of Science, and Ovid MEDLINE. Ten studies were included; all of them included patients with obesity and provided a whole‐brain analysis of grey matter (GM) distribution. Our findings confirmed the most consistent GM reductions in patients with obesity in the left, middle, and right inferior frontal gyrus (including the insula), the left middle temporal cortex, the left precentral gyrus, and the cerebellum. On the other hand, increased GMV in patients with obesity were found in the left cuneus, left middle frontal gyrus, left inferior occipital gyrus, and corpus callosum.